Bridging Divine Accountability And Stakeholder Theory: An Islamic Maqasid Al-Shariah Framework For ESG Performance - Nabila Rizka Awalia; Baiq El Badriati; Ummu Rosyidah (Universitas Islam Negeri Mataram, 2025)
This study aims to address a fundamental issue in contemporary Environmental, Social, and Governance (ESG) practice: the tendency towards instrumentalism and the phenomenon of greenwashing. It proposes the integration of Islamic ethical principles, specifically Maqasid al-Shariah and Divine Accountability, into the corporate governance framework to establish a more robust philosophical foundation for business sustainability. Employing a library research method with a critical conceptual analysis approach, this study analyzes three bodies of literature: (1) theories and critiques of conventional ESG, (2) principles of Islamic business ethics, and (3) global sustainability reporting standards. The result is an integrative framework that positions Divine Accountability as the foundation for intrinsic motivation, utilizes the five objectives of Maqasid al-Shariah (hifzh al-din, nafs, 'aql, nasl, mal) as an operational lens, and applies them within ESG decision-making processes. This framework offers a solution to greenwashing by emphasizing authenticity, transparency, and value consistency. The findings indicate that a Maqasid-based approach not only enriches the discourse on sustainable governance but also provides practical guidance for companies, particularly within the context of Islamic economies, to achieve more authentic and integral ESG performance. Keywords: Maqasid al-Shariah, ESG, Corporate Governance, Divine Accountability, Greenwashing, Islamic Business Ethics.